Board Structure, CEO Equity-Based Compensation, and Financial Performance: Evidence from MENA Countries - Abdullah A. Aljughaiman; Abdulateif A. Almulhim; Abdulaziz S. Al Naim (International Journal of Financial Studies, 2024)
This paper investigates the association between board of director (BOD) structures and CEO equity-based compensation (long-term incentive) for commercial banks (conventional and Islamic banks) in MENA countries. Specifically, we take board size and board independence to measure the board structure. Furthermore, we investigate the influence of board structure on the association between CEO equity-based compensation and financial performance. Moreover, we compare conventional and Islamic banks in testing these relationships. Using a sample of 65 banks in MENA countries for the period between 2009 and 2020, we show a significant positive association between board size and CEO compensation. However, we find the same association between these variables for IBs, but the effect of board size on CEO compensation is less. We also show that board independence is negatively correlated with CEO compensation. Nevertheless, the relationship between board independence and CEO ownership is positive for IBs. For the moderating test, we find that effective board structure provides more incentives to the CEO, leading them to achieve higher financial performance. The Islamic bank’s business model (based on Shari’ah principles) contributes to the different influences of board structure on CEO compensation. Our results provide the insight that a strong and effective board is important for managing the executive’s compensation system. The findings of this study have implications for financial firms, policymakers, and regulators. Specifically, the study may help in understanding the benefits of different compensation structures relative to different types of financial firms.